Diagnostic Imaging of Congenital Heart Defects : Diagnosis and Image-Guided Treatment. - Gutberlet, Matthias (Thieme Medical Publishers, Incorporated, 2019)
A valuable new reference in the diagnosis and image-guided treatment of congenital heart defects Congenital heart defects represent the most common birth defect and affect millions of children worldwide. Defects of the heart and great vessels span a broad spectrum. Modern medical progress has enabled more than 90% of patients to reach adulthood. In many cases, however, patients remain ill throughout their lives, with significant limits on quality of life and physical capacity. Our ongoing goals are to improve treatment options even further. This book details all important imaging techniques fo.